2017
DOI: 10.1002/esp.4186
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional numerical modeling of the Bulle effect: the nonlinear distribution of near‐bed sediment at fluvial diversions

Abstract: The Bulle effect is a phenomenon in which a disproportionately higher amount of near‐bed sediment load at a fluvial diversion moves into the diverted channel, even for cases in which the proportion of water (with respect to the main flow) entering the diversion channel is relatively small. This phenomenon has wide‐ranging implications for both engineered and natural systems: from efficient design of channels to redirect water and sediment for reclaiming sinking deltas, designing navigational channels that do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…The effect was quantified on diversions where one channel laterally branches off at a given angle from the main channel, which continues on a straight path. Research on these diversions has shown that a disproportionate amount of bedload sediment enters the diversion channel compared to the water discharge ratio between the two channels (Bulle, 1926;Dutta et al, 2017). The amount of bedload entering the diversion channel increases as the diversion angle increases from~10 to 120° (Bulle, 1926;Dutta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect was quantified on diversions where one channel laterally branches off at a given angle from the main channel, which continues on a straight path. Research on these diversions has shown that a disproportionate amount of bedload sediment enters the diversion channel compared to the water discharge ratio between the two channels (Bulle, 1926;Dutta et al, 2017). The amount of bedload entering the diversion channel increases as the diversion angle increases from~10 to 120° (Bulle, 1926;Dutta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research on these diversions has shown that a disproportionate amount of bedload sediment enters the diversion channel compared to the water discharge ratio between the two channels (Bulle, 1926;Dutta et al, 2017). The amount of bedload entering the diversion channel increases as the diversion angle increases from~10 to 120° (Bulle, 1926;Dutta et al, 2017). This phenomenon is associated with near-bed flow being diverted into the diversion channel, which is responsible for transporting bedload into the channel, and near-surface flow primarily continuing into the main channel (Bulle, 1926;Dutta et al, 2017;Dutta and Garcia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…; Dutta et al. ). If flow separation occurs, the influence of the Bulle effect on the sediment partitioning seems small compared to the influence of the flow separation zone (De Heer and Mosselman, ; Van der Mark and Mosselman, ).…”
Section: Introductionmentioning
confidence: 98%
“…), sediment diversion due to the bifurcation angle (Bulle, ; Van der Mark and Mosselman, ; Dutta et al. ), partitioning of suspended load (Slingerland and Smith, ; Edmonds and Slingerland, ; Gaweesh and Meselhe, ), mixed sediment processes (Sloff et al. ; Frings and Kleinhans, ; Sloff and Mosselman, ; Kästner et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation